2019
DOI: 10.1097/dss.0000000000001971
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 3 New Resilient Hyaluronic Acid Fillers, Crosslinked With Decreased BDDE, for the Treatment of Dynamic Wrinkles: Results of an 18-Month, Randomized Controlled Trial Versus Already Available Comparators

Abstract: BACKGROUND Three new hyaluronic acid (HA)-based fillers made of long chains crosslinked with reduced amounts of 1,4-butanediol diglycidyl ether (BDDE) were developed for the treatment of dynamic facial areas. Their resilience and increased stretching ability were optimized to ease injectors' practice and provide patients with most natural aesthetic results. OBJECTIVE This study aimed at evaluating the efficacy, durability, and safety of these resilient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…On the other hand, some tardive inflammatory phenomenon have been advocated to be related to BDDE concentration, in fact, some studies have tried to show an higher safety and biocompatibility of HA filler with decreased BDDE. Moreover, decreased BDDE has been advocate as capable of increase filler elasticity and get more natural results [9]. In 2014, in Europe, for the first time, a HA filler containing PEG as cross-linking agent was introduced in the market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some tardive inflammatory phenomenon have been advocated to be related to BDDE concentration, in fact, some studies have tried to show an higher safety and biocompatibility of HA filler with decreased BDDE. Moreover, decreased BDDE has been advocate as capable of increase filler elasticity and get more natural results [9]. In 2014, in Europe, for the first time, a HA filler containing PEG as cross-linking agent was introduced in the market.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors have contributed to BDDE becoming the industry-standard crosslinker [8]. However, recent studies about tardive inflammatory phenomenon following HA filler injection have pointed out the hypothesis that degradation of cross-linked HA filler may expose trace substances of BDDE that can induce inflammatory phenomenon characterized by tardive swelling or nodule development [9]. In the past years, a new cross-linking agent has been used in order to stabilize HA chains in HA filler industry: The poly (ethylene glycol) also known as PEG.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that these products (RHA 2, 3, 4) are able to adapt to facial movements to treat dynamic wrinkles and folds, a typical indication for neuromodulators [98] . Recently FDA approved for the correction of deep dynamic wrinkles, including the nasolabial folds; RHA 2 and 3 are indicated for injection into the mid-to-deep dermis, while RHA 4 is indicated for injection into the deep dermis to superficial subcutaneous tissue [99] . One split-face, randomized controlled trial on 90 subjects with moderate to severe nasolabial folds found at least equivalent efficacy and safety profiles with comparable fillers [100] .…”
Section: Discussionmentioning
confidence: 99%
“…Several published clinical trials have demonstrated the safety and tolerability of the range and have established the clinical effectiveness of specific formulations for various indications. 16,17,[19][20][21][22]…”
Section: Introductionmentioning
confidence: 99%